Who Makes Revolution in the Age of Speculative Design? - Chukhrov, Keti (Stasis, 2018)
Contemporary theories of social emancipation contend that it is time to dispense with the concept of revolution and leave it merely as the legacy of political struggles belonging to the age of industrial economy. Today’s globalization, semio-capital, speculative design, crypto-economy, and artificial intelligence would engage epistemologically different emancipatory lexicons and techniques of resistance. All new futurisms posit technological solutions for hitherto political stakes. What remains unheeded in them is the existential need for cognitive equality and social continuity with the masses in constructing the collective subject of emancipation. Recent election results in the U.S., U.K., Eastern Europe, and Russia diagnose an immense cognitive rupture between the producers of emancipatory lexicons and disadvantaged workers. Such a split between mind and body was already made apparent in Hegel’s dialectics of lord and bondsman. In order to surpass this split, it is of utmost importance to reconsider the conditions in which the premature construction of the proletariat took place in the context of the October revolution. The proletariat was posited in this case not only as revolutionary subject, but as the principal subject of Enlightenment as well.